2010
DOI: 10.1104/pp.109.151035
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Cadmium from Culture to Spikelet: Noninvasive Imaging and Quantitative Characterization of Absorption, Transport, and Accumulation of Cadmium in an Intact Rice Plant    

Abstract: We characterized the absorption and short-term translocation of cadmium (Cd) in rice (Oryza sativa 'Nipponbare') quantitatively using serial images observed with a positron-emitting tracer imaging system. We fed a positron-emitting 107 Cd (halflife of 6.5 h) tracer to the hydroponic culture solution and noninvasively obtained serial images of Cd distribution in intact rice plants at the vegetative stage and at the grain-filling stage every 4 min for 36 h. The rates of absorption of Cd by the root were proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
152
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(179 citation statements)
references
References 28 publications
20
152
0
3
Order By: Relevance
“…long culms and high spikelet number, could have reduced Cd partitioning to grain. Indeed, it was found that Cd translocation within the xylem is slowed down by binding to cell walls and by accumulation in the nodes, so that tall varieties with long spikes are less prone to accumulate Cd in grain (Kubo et al 2008, Fujimaki et al 2010, Quinn et al 2011.…”
Section: Resultsmentioning
confidence: 99%
“…long culms and high spikelet number, could have reduced Cd partitioning to grain. Indeed, it was found that Cd translocation within the xylem is slowed down by binding to cell walls and by accumulation in the nodes, so that tall varieties with long spikes are less prone to accumulate Cd in grain (Kubo et al 2008, Fujimaki et al 2010, Quinn et al 2011.…”
Section: Resultsmentioning
confidence: 99%
“…Positron emitters, which are widely used in the medical imaging technique of positron emission tomography, have been applied to plant research [3,4]. A positron emitted from the sample couples with an electron in the tissue and converts it into two identical g-rays, a phenomenon called annihilation.…”
Section: Introductionmentioning
confidence: 99%
“…This system enables monitoring of the real-time movement of the tracer in living plants as a video, and also quantitative analysis of the movement of substances by freely selecting a region of interest (ROI) on the image data obtained. Recently, a realtime imaging system for Cd using positron-emitting 107 Cd tracer and PETIS was established (Fujimaki et al 2010). Ishikawa et al (2011) improved the design of the root box and realised direct observation of Cd uptake by the roots in solution culture, and characterised clearly the differences in Cd dynamics from the culture solution to the grains between high-and low-Cd accumulating rice cultivars.…”
mentioning
confidence: 99%
“…However, only the static distribution of Cd at a given moment can be obtained by autoradiography. In recent years, the positron-emitting tracer imaging system (PETIS) has been employed to study the uptake and translocation of metals using the positronemitting tracers 52 Mn (Tsukamoto et al 2006), 62 Zn (Suzuki et al 2008), 52 Fe (Tsukamoto et al 2009) and 107 Cd (Fujimaki et al 2010) in intact living plants. This system enables monitoring of the real-time movement of the tracer in living plants as a video, and also quantitative analysis of the movement of substances by freely selecting a region of interest (ROI) on the image data obtained.…”
mentioning
confidence: 99%